MIGRATORY STOMATITIS - CASE PRESENTATION - Ana Maria Filioreanu; Cristina Popa; George Alexandru Maftei; Ioanina Parlatescu; Carmen Larisa Nicola; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2019)
Migratory stomatitis is a rare recurring condition of unknown etiology that mainly involves lingual mucosa, with a typical appearance of geographic tongue. Factors such as heredity, nutritional deficiencies or stress may be the contributing factors to the appearance of lesions. Clinically, they appear as circular, multiple, erythematous lesions with red spots surrounded by a white, narrow, hyperkeratotic aspect with irregular, slightly elevated appearance modifying its form in 24 hours.The condition may have spectacular clinical signs when the lesions are localised on the tongue, and may involve other areas of oral mucosa, such as labial or floor of mouth mucosa. The aim of this study is to present a clinical case of a patient with two localisations of lesions corresponding clinically to migratory stomatitis. The anatomopathological examination confirmed the migratory stomatitis diagnosis, so we could begin the specific treatment, to which the patient responded positively.